"Makanlah Nasi! (Eat Rice!)": Colonial Cuisine and Popular Imperialism in The Netherlands During the Twentieth Century. Issue 1 (2nd January 2017) - Kuipers, Matthijs
Abstract: This article analyzes the role of colonial foodways in Dutch metropolitan imperial culture. The interaction between material life, cultural values, and imperial ideologies remains a relative blind spot in our understanding of Dutch imperialism. The cuisine from the Dutch East Indies, which found its way to The Netherlands around the turn of the twentieth century, was a decidedly colonial invention and was a reflection of the racial and gendered colonial order of the time. Attempts to popularize the rijsttafel (rice table) in the metropole in the early years of the twentieth century proved unsuccessful, which presents us with one of the paradoxes of "home imperialism": there was tacit metropolitan consent to imperialism, if not active participation in it, but simultaneously the imperial-mindedness of the metropolitan public was quite low. It is a paradox that puzzled contemporaries and latter-day historians alike, but it can be resolved if we see indifference – in this case indifference to colonial cuisine – not as an anomaly but as a consequence of the imperial mind-set that allowed for conceptualizing the metropole as immune to influences from the colonies. Thus seen, indifference is an act of imperialism.